2015
DOI: 10.1038/ncomms9056
|View full text |Cite|
|
Sign up to set email alerts
|

Low-threshold amplified spontaneous emission and lasing from colloidal nanocrystals of caesium lead halide perovskites

Abstract: Metal halide semiconductors with perovskite crystal structures have recently emerged as highly promising optoelectronic materials. Despite the recent surge of reports on microcrystalline, thin-film and bulk single-crystalline metal halides, very little is known about the photophysics of metal halides in the form of uniform, size-tunable nanocrystals. Here we report low-threshold amplified spontaneous emission and lasing from ∼10 nm monodisperse colloidal nanocrystals of caesium lead halide perovskites CsPbX3 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

53
1,513
10
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 1,420 publications
(1,580 citation statements)
references
References 56 publications
53
1,513
10
4
Order By: Relevance
“…Our initial study focused on CsPbBr 3 nanowires, as previous reports suggest this composition is strongly photoluminescent (26,34) and capable of stimulated emission (29)(30)(31). Although we have already reported the synthesis of colloidal CsPbBr 3 nanowires (34), those nanowires are too narrow (∼20-nm diameter) to efficiently confine the 535-nm emission and are therefore unable to support photonic lasing (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our initial study focused on CsPbBr 3 nanowires, as previous reports suggest this composition is strongly photoluminescent (26,34) and capable of stimulated emission (29)(30)(31). Although we have already reported the synthesis of colloidal CsPbBr 3 nanowires (34), those nanowires are too narrow (∼20-nm diameter) to efficiently confine the 535-nm emission and are therefore unable to support photonic lasing (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas early studies revealed wide stoichiometric emission wavelength tunability (28), stimulated emission for all-inorganic perovskites was not reported until 2007 in thin films of CsPbBr 3 (29,30). Recent reports have expanded the versatility of the cesium lead halides by demonstrating amplified spontaneous emission in a variety of CsPbX 3 compositions and alloys, as well as whispering gallery mode lasing in coated silica beads and microcrystals (31)(32)(33). Whereas these recent works have highlighted the impressive properties of cesium lead halide perovskites in terms of their optical properties and tunability, the growth and characterization of cesium lead halide nanowires capable of lasing has not yet been achieved.…”
mentioning
confidence: 99%
“…[1][2][3][4] Of high interest are their remarkable optical properties such as non-linear absorption, stimulated emission and blinking behavior. 2,[5][6][7] Compared to classical Cd-based chalcogenide quantum dots (QDs), CsPbX 3 (X = Cl, Br, I) offer a very broad and easily adjustable composition versatility together with ample options for shape control, which allow tuning of their emission wavelength throughout the whole visible spectrum. [8][9][10][11][12][13][14] Among other applications, such highly luminescent and spectrally tunable NCs are ideally suited to produce monochromatic and white LEDs (WLEDs).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, HPVKs layers have been successfully applied in a wide range of photonic devices, such as photodetectors [91,92] or light emitting diodes [90,93]. In addition, since HPVKs present a fast carrier formation and long recombination time, they are promising materials to reduce the stimulated emission threshold in active devices [94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109], as it has been nicely reviewed in [90].…”
Section: -P14mentioning
confidence: 99%
“…Spherical perovskite nanocrystals have also been synthesized as a promising material to implement active devices. Yakunin et al studied the properties of CsPbX 3 colloidal perovskite nanoparticles and its incorporation in different photonics structures [105]. By altering the composition X it became possible to modify the bandgap between 450 and 700 nm (see Fig.…”
Section: -P15mentioning
confidence: 99%